1992
DOI: 10.3109/00952999208992835
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Compliance after Detoxification among Highly Disadvantaged Alcoholics

Abstract: An outcome study was carried out on a series of 109 highly disadvantaged alcoholics discharged from the detoxification unit of a large municipal hospital in New York City. We examined the impact of a variety of clinical and demographic factors on retention in the initial phases of outpatient and inpatient treatment following discharge. Both high school completion and a history of at least 6 months of employment in the two years preceding admission correlated with frequency of registration for continued afterca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
5

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 32 publications
1
10
0
5
Order By: Relevance
“…Supporting these assertions, the present finding is in line with several prospective studies of alcoholism and other substance use disorders in which Trails B was predictive of participation in aftercare sessions and length of hospital stay during inpatient treatment [36,37]. Our negative finding on the WCST is consistent with a study which found that WCST scores did not differ between treatment completers and dropouts in the treatment of cocaine dependence [18].…”
Section: Discussionsupporting
confidence: 82%
“…Supporting these assertions, the present finding is in line with several prospective studies of alcoholism and other substance use disorders in which Trails B was predictive of participation in aftercare sessions and length of hospital stay during inpatient treatment [36,37]. Our negative finding on the WCST is consistent with a study which found that WCST scores did not differ between treatment completers and dropouts in the treatment of cocaine dependence [18].…”
Section: Discussionsupporting
confidence: 82%
“…6,[21][22][23][24][25] Obstacles to sobriety include psychiatric illness, poor social support, lack of stable housing, duration of addiction and refusal of treatment.…”
mentioning
confidence: 99%
“…It has been reported to affect 53%-73% of homeless adults, [1][2][3] with a high frequency of heavy alcoholism (i.e., > 20 drinks/day). [4][5][6] Because of its availability and low cost, nonbeverage alcohol (e.g., mouthwash) is commonly used. 7,8 People with chronic alcoholism are frequent users of crisis health services such as the emergency department (ED);…”
mentioning
confidence: 99%
“…Although simple medical detoxification without subsequent rehabilitation leads to no long term improvement except in very few patients (5% in the study of Wieser & Kunad 1965), even highly disadvantaged alcoholics can be convinced to follow the necessary aftercare when adequate motivational treatment is applied. This was recently shown by Castaneda et al (1992). Their study of 109 highly disadvantaged patients merits special attention.…”
Section: New Motivatioiial Treatment Approachesmentioning
confidence: 95%